CURE Dataset: Ladder Networks for Audio Event Classification - Dubey, Harishchandra; Emmanouilidou, Dimitra; Tashev, Ivan (2019 IEEE Pacific Rim Conference on Communications, Computers and Signal Processing (PacRim), 2019)
Audio event classiﬁcation is an important task for several applications such as surveillance, audio, video and multimedia retrieval etc. There are approximately 340 million people with hearing loss who can’t perceive events happening around them. This paper establishes the CURE dataset which contains curated set of speciﬁc audio events most relevant for people with hearing loss. It is formatted as 5 sec sound recordings derived from the Freesound project. We propose a ladder network based audio event classiﬁer. We adopted the state-of-the-art convolutional neural network (CNN) embeddings as audio features for this task. We start with signal and feature normalization that aims to reduce the mismatch between different recordings scenarios. Initially, a CNN is trained on weakly labeled Audioset data. Next, the pre-trained model is adopted as feature extractor for proposed CURE corpus. We also explore the performance of extreme learning machine (ELM) and use support vector machine (SVM) as baseline classiﬁer. As a second evaluation set we incorporate ESC-50. Results and discussions validate the superiority of Ladder network over ELM and SVM classiﬁer in terms of robustness and increased classiﬁcation accuracy.